Racial Disparity in Anthracycline-induced Cardiotoxicity in Breast Cancer Patients - Swetha Balaji; Antu K. Antony; Harry Tonchev; Giorgia Scichilone; Mohammed Morsy; Hania Deen; Imaduddin Mirza; Mohamed M. Ali; Abeer M. Mahmoud (Biomedicines, 2023)
Breast cancer has become the most common cancer in the US and worldwide. While advances in early detection and treatment have resulted in a 40% reduction in breast cancer mortality, this reduction has not been achieved uniformly among racial groups. A large percentage of non-metastatic breast cancer mortality is related to the cardiovascular effects of breast cancer therapies. These effects appear to be more prevalent among patients from historically marginalized racial/ethnic backgrounds, such as African American and Hispanic individuals. Anthracyclines, particularly doxorubicin and daunorubicin, are the first-line treatments for breast cancer patients. However, their use is limited by their dose-dependent and cumulative cardiotoxicity, manifested by cardiomyopathy, ischemic heart disease, arrhythmias, hypertension, thromboembolic disorders, and heart failure. Cardiotoxicity risk factors, such as genetic predisposition and preexisting obesity, diabetes, hypertension, and heart diseases, are more prevalent in racial/ethnic minorities and undoubtedly contribute to the risk. Yet, beyond these risk factors, racial/ethnic minorities also face unique challenges that contribute to disparities in the emerging field of cardio-oncology, including socioeconomic factors, food insecurity, and the inability to access healthcare providers, among others. The current review will address genetic, clinical, and social determinants that potentially contribute to this disparity.